Surfside sisters - Thayer, Nancy, 1943- (Ballantine Books, 2019)
A woman from Nantucket returns home to find that reunions aren't always so simple in this heartwarming novel from the New York Times bestselling author of A Nantucket Wedding and Secrets in Summer. Growing up, Lara always dreamed of leaving Nantucket to become a writer. Now that she's a bestselling novelist living in New York City, she realizes that success isn't what she thought it would be. Confused, and with a harrowing case of writer's block, Lara misses the island way of life more than ever. But going back to Nantucket out of the blue isn't so easy, as a deep rift with her childhood best friend, Isabelle, has kept the two from speaking for years. When her mother is laid off from her job and becomes depressed, Lara reluctantly comes home, leaving a failed relationship and hopefully her other troubles behind. But facing her estranged best friend is harder than she expects. And falling for Isabelle's brother, Sebastian--who was also Lara's teenage crush--only complicates things. Lara soon realizes that she must remedy the mistakes of her past in order to find true happiness.